Revitalising public awareness of the Seputih Mayang site as a cultural heritage in Jember Regency from 1996 to 2012 - Bahar, Madjid Fahdul; Suci, Wike Cahyani; Towilah, Lailatul; Salsabila, Nurista; Utami, Nita Dwi (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2024)
It seems as if the relics of the megalithic era will never fade over time. This can be seen from several relics that have distinctive characteristics, especially the relics at the Seputih  Site.  The Seputih site in  Seputih Mayang Village seems to be a witness that there was prehistoric life that can still be seen today. The discovery of sarcophagi and dolmens, which can be seen and examined from a distance, shows that at that time there were already animist beliefs and dynamism, as indicated by the presence of stone tombs and places to worship the spirits of their ancestors. These discoveries from the past are certainly a legacy that must be safeguarded by today's society by preserving these relics as completely as possible. Through this article, we will discuss the efforts of community awareness in preserving the  Seputih  Mayang site as a cultural heritage from the megalithic period during the 1996-2012 period.